2020
DOI: 10.1016/j.hpb.2019.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative imaging characteristics predict poor survival and inadequate resection for left-sided pancreatic adenocarcinoma: a multi-institutional analysis

Abstract: Background: Optimal treatment of pancreatic ductal adenocarcinoma of the neck, body and tail (PDAC-NBT) necessitates R0 surgical resection. Preoperative radiographic identification of patients likely to achieve successful oncologic resection remains difficult. This study seeks to identify preoperative imaging characteristics predictive of non-R0 resections or impaired survival for PDAC-NBT.Methods: Patients at five high-volume centers who underwent resection for PDAC-NBT were retrospectively analyzed. The most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The present study also showed a poor prognostic impact of radiologic SVs invasion in anatomically resectable left-sided PDAC. In contrast, a recently published multicenter study reported that on preoperative imaging, patients with tumors interfacing with the SV did not have a worse survival, although they achieved fewer R0 resections ( 37 ). The authors claimed that vascular invasion is not in itself a marker of worse tumor biology, but rather, it reflects the likelihood of an incomplete resection, which is correlated with worse survival outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…The present study also showed a poor prognostic impact of radiologic SVs invasion in anatomically resectable left-sided PDAC. In contrast, a recently published multicenter study reported that on preoperative imaging, patients with tumors interfacing with the SV did not have a worse survival, although they achieved fewer R0 resections ( 37 ). The authors claimed that vascular invasion is not in itself a marker of worse tumor biology, but rather, it reflects the likelihood of an incomplete resection, which is correlated with worse survival outcomes.…”
Section: Discussionmentioning
confidence: 95%